THE USE OF INDUCTIVE AND DEDUCTIVE METHODS IN WORKING WITH PRESCHOOL OLDER CHILDREN - Mirazimova Muxabbat (Web of Journals Publishing, 2024)
This article reflects on the use of inductive and deductive methods in working with preschool adults, the comprehensive development of children.
Keywords: Education, inductive, child education, method, perfection, deductive, older age, development, trait, process of activities, ability.